1978
DOI: 10.1002/hlca.19780610715
|View full text |Cite
|
Sign up to set email alerts
|

«Push‐Pull»‐Acetylene als Hilfsmittel zur Synthese von Amiden

Abstract: Amide Synthesis by Means of 'Push-Pull'-AcetylenesSummary 'Push-pull'-acetylenes react easily with carbon acids. Addition of amines to the crude reaction mixture gives amides in an excellent yield by a simple one-pot procedure. Because of the high selectivity of the acetylenes 1 towards carboxylic functions and of the high selectivity of the enol esters 4 towards amine functions, 'pushpull'-acetylenes could be excellent reagents for peptide synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…On the other hand, if – OAc attacks the α-site of the enamine, intermediate C is probably obtained (path b) and consequently undergoes elimination to give D . Finally, the amide product 4 can be obtained by rearrangement of α-acyloxylation intermediate D through protonation intermediate E …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, if – OAc attacks the α-site of the enamine, intermediate C is probably obtained (path b) and consequently undergoes elimination to give D . Finally, the amide product 4 can be obtained by rearrangement of α-acyloxylation intermediate D through protonation intermediate E …”
mentioning
confidence: 99%
“…Cation intermediate B then is pronated to afford the β-acyloxylation product 3. On the other hand, if − OAc attacks the α-site of the enamine, intermediate C is probably obtained (path b) and consequently undergoes elimination to give D. Finally, the amide product 4 can be obtained by rearrangement of α-acyloxylation intermediate D through protonation intermediate E. 16 To better understand the mechanism, several control and isotopic labeling experiments were investigated (Scheme 5). First, we carried out the reaction using 18 O-labeled water (Scheme 5a).…”
mentioning
confidence: 99%
“…Compared with isoxazolium salts 4 [39][40] [41] and ynamines 12 [12] [14], PPacetylenes 1 could offers everal advantages as peptide reagents: Comparedw ith ynamines, their characteristicsa re al owerb asicity,a sw ell as ah igher selectivity. First experiments showed that carboxylic amidesc oulde asily be prepared in as imple one-potr eaction by adding carboxylic acids to the new PP-acetylenesinafirst step,followed by adding the amine to the same solution in asecond step [35]. 7.…”
Section: Scheme 13mentioning
confidence: 99%